Methylation Alkynylation of Terminal Alkenes via 1,2-Alkynyl Migration Using Dicumyl Peroxide as the Methyl Source - Qin, Yi-qun; Chen, De; Liu, Liang; Zhang, Jia-jia; Peng, Xin-ju; Luo, Yong-yue; Deng, Wei; Xiang, Jiannan (Synthesis, 2021)
The metal-free oxidative alkene methylation/alkynylation of 1,4-enyn-3-ols with an organic peroxide as the methyl source has been developed, which provides straightforward and practical access to the challenging quaternary-carbon-containing but-3-yn-1-ones. The method is reasoned to go through methylation of functional alkenes utilizing dicumyl peroxide as the methylating reagent and subsequent intermolecular cyclization/1,2-alkynyl migration. This reaction has an excellent functional group tolerance, broad substrate scope, and exquisite selectivity.
Keywords: alkene difunctionalization; migration reaction; radical